Tutoring in Positive Prevention - the Way to Strengthen Resilience and Positive Youth Development - Jana Maria Chojecka (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction What works in prevention is a main question for evidence based practice. Instead of focusing on risk factors and deviant behaviors we need to strengthen individual and social protective factors. It leads to new solutions in prevention practice. Research Aim The main purpose of this article is to discuss the possibility to use tutoring, especially peer tutoring for activating resilience processes and positive youth development. It seems interesting to see how at-risk youth can be peer tutors. Evidence-Based Facts Tutoring is most effectively used in education (not only academic) and is beneficial for both tutors and tutees. There is great need to investigate how effective peer tutoring  involving at-risk youth as tutors can be. Research findings confirm that low-achieving students can be effective tutors (Cohen i in.,1982, Giesecke, Cartledge,1993), but there is lack of data how this kind of tutoring can be used in prevention in general. Summary Because new approach in prevention has emerged (positive youth development instead of deficit perspective) it is important for researchers as well as for practitioners to find useful factors and mechanisms which can be used to build resilience among children and youth. Tutoring seems to be one of this method. There is a great need to investigate the effectiveness of prevention programs where children at-risk are peer tutors.